Bibliometric Analysis of Research on Visual Impairment and Blindness: 2013-2022 - Aulianto, Dwi Ridho; Karolina, Cut Meutia (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2024)
This study aims to find out more details about the Journal of Visual Impairment and Blindness (JVIB) published in 2013–2022, as seen from the distribution of documents per year, document type, open access type, author country, productive authors, citation analysis, article citation rate, journal cite score rate, publication trends based on keyword occurrence, and publication trends by year. The research employs bibliometric analysis, gathering data from the Scopus database on June 13, 2023. Data is then processed and analyzed using the Publish or Perish (PoP) and VOSviewer applications to visualize the results. The results concluded that JVIB is a reputable international journal with a Q3 rating managed by the American Foundation for the Blind (AFB) with a frequency of publication of six times in one volume. A total of 686 documents have been published from 2013 to 2022, divided into articles, notes, editorials, letters, erratums, and reviews. America is the most dominant country, contributing a total of 490 documents. Emerson, R.W., became the most productive author with 50 documents. JVIB was cited 2710 times, with a per-article citation rate of 271.00, an h-index of 21, a g-index of 31, an hI, norm 12, HLA of 1.20, and hA-index 5. The current publication trend identified publications discussing vision rehabilitation.